The Role of Trisakti University Students in Enhancing Community Resources in Ciambar Village, Sukabumi, through Independent Entrepreneurial Activities in Applied Science and Technology or Kuliah Usaha Mandiri Ilmu Teknologi Terapan (KUM-ITT) - Nurhayati, Nurhayati; Muhammad Fahurrahman; Khusnul Ramadhan Eka Putri; Syahla Larrissa; Cicilia Benita Putri Patricia; Aisyah Nurkhansa Putri; Anisa Suci Ramadhana; Estevania Wise Maharani (CV. AFDIFAL MAJU BERKAH, 2024)
Kuliah Usaha Mandiri Ilmu Teknologi Terapan (KUM-ITT) program is an initiative that integrates education, research, and community service into a cohesive field activity aligned with the objectives and content of the curriculum. This program bridges theory with practice in social life beyond the campus. KUM-ITT is designed to provide students with the opportunity to experience life within a community. By directly interacting with the community, KUM-ITT participants are tasked with uncovering potential and addressing social issues in the village. Ciambar Village in Sukabumi Regency is one of the target areas for the KUM-ITT activities. In 2008, based on Regional Regulation No. 5 of 2008, Ciambar Village was divided into Ciambar and Cibunarjaya Villages. Surveys have identified several challenges faced by the residents of Ciambar Village, including issues related to infrastructure, health, economy, environment, and others. To address these challenges, five work programs have been established: Community Welfare Improvement, Awareness of Healthy and Clean Living, Infrastructure Empowerment, Women's and Housewives Empowerment, and Children’s Empowerment. The activities were conducted from July 2 to July 22, 2024. All planned programs were successfully implemented as intended and anticipated.